Preoperative Neutrophil Lymphocyte Ratio in Prediction of Adnexal Mass Torsion. (25th February 2023) - Ghimire, Asmita; Ghimire, Sailaja; Shrestha, Asmita; Pant, Samriddha Raj; Subedi, Nilam; Pant, Padam Raj
Abstract : Aims . Adnexal torsion commonly affects reproductive age group females. Prompt diagnosis and early management help in the preservation of fertility. However, its diagnosis is challenging. Preoperative diagnosis can be suspected in only 23–66% of the cases and half of the patients operated for adnexal torsion have different diagnosis. This article thus aims to identify the diagnostic value of preoperative neutrophil lymphocyte ratio in adnexal torsion in comparison with other untwisted unruptured ovarian cysts. Methods . This was a retrospective study conducted in the duration of five years from 1st January 2016 to 1st January 2020. The data about demographic parameters, hematological parameters, operative approach, operative technique, and histopathological reports were derived from an electronic database and documented on proforma. SPSS was used for statistical analysis. Logistic regression analysis and influence of each factor on preoperative diagnosis of Adnexal torsion was evaluated. Results . A total of 125 patients were included in the article (adnexal torsion group n  = 25, untwisted unruptured ovarian cyst group n  = 100). There was no statistically significant difference in comparison to age, parity, and abortion between both groups. Most patients had undergone laparoscopic surgery which was based on surgeon's skill and preference. Nineteen (78%) patients in the adnexal torsion group underwent oophorectomy while infarcted ovary was seen in only 4 cases. Among the blood parameters, only neutrophil-lymphocyte ratio (NLR) >3 was found to be statistically significant under logistic regression analysis. Most common adnexal pathology to undergo torsion was serous cyst. Conclusion . Preoperative neutrophil-lymphocyte ratio can be a predictive marker for diagnosis of adnexal torsion and can differentiate it from untwisted unruptured ovarian cysts.